2020
DOI: 10.3390/cancers12030532
|View full text |Cite
|
Sign up to set email alerts
|

Role of Akt Activation in PARP Inhibitor Resistance in Cancer

Abstract: Poly(ADP-ribose) polymerase (PARP) inhibitors have recently been introduced in the therapy of several types of cancers not responding to conventional treatments. However, de novo and acquired PARP inhibitor resistance is a significant limiting factor in the clinical therapy, and the underlying mechanisms are not fully understood. Activity of the cytoprotective phosphatidylinositol-3 kinase (PI3K)-Akt pathway is often increased in human cancer that could result from mutation, expressional change, or amplificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 146 publications
(181 reference statements)
1
40
0
1
Order By: Relevance
“…In turn, a cytoprotective signalosome (p-ATM–NEMO–Akt–mTOR) is formed, which induces the activation of Akt. Akt is a “master regulator” of various cell-survival pathways; its activation produces a cytoprotective phenotype ( 26 ).…”
Section: Parp Activation a Reemerging Pathophysiological Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, a cytoprotective signalosome (p-ATM–NEMO–Akt–mTOR) is formed, which induces the activation of Akt. Akt is a “master regulator” of various cell-survival pathways; its activation produces a cytoprotective phenotype ( 26 ).…”
Section: Parp Activation a Reemerging Pathophysiological Conceptmentioning
confidence: 99%
“…Multiple lines of in vivo experiments have demonstrated that pharmacological PARP inhibitors or PARP1 deficiency can significantly improve the outcomes of various animal models of acute and chronic lung injury, including endotoxin- or sepsis-induced lung injury, pancreatitis-induced lung injury, lung inflammation elicited by various agents (e.g., zymosan, carrageenan or elastase), ventilator-induced lung injury, environmental agent– or drug-induced lung injury, or lung fibrosis and allergy/asthma–associated lung inflammation and dysfunction ( 26 84 ). Table 1 focuses on the findings related to the effect of PARP inhibitors in various forms of ALI and lung inflammation.…”
Section: The Therapeutic Efficacy Of Parp Inhibitors In Alimentioning
confidence: 99%
“…Interestingly, nicotinamide has a close relationship with poly (ADP-ribose) polymerase (PARP) (81,87) that is also tied to mTOR and Akt (287,288). PARP is a nuclear protein that binds to DNA strand breaks and cleaves NAD + into nicotinamide and ADP-ribose.…”
Section: Nicotinamide and The Downstream Pathways Of Mtormentioning
confidence: 99%
“…For example, preliminary data demonstrated a synergistic effect of capivasertib in combination with olaparib, indicating that inhibitors of the P13K/AKT pathway potentiate a cytostatic effect of poly ADP-ribose polymerase (PARP) inhibitors in a combination therapy. 65 Recently, Lee et al performed a biomarker-based umbrella trial (VIKTORY; targeted agent eValuation In gastric cancer basket KORea) in GC. 35 This study classified patients with metastatic GC based on eight different biomarker groups and, among 10 associated clinical trials, included a treatment arm with capivasertib plus paclitaxel for PIK3CA mutation.…”
Section: Capivasertib (Azd5363)mentioning
confidence: 99%